2001
DOI: 10.1046/j.1432-1327.2001.02146.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational model for the consensus V3 loop of the envelope protein gp120 of HIV‐1 in a 20% trifluoroethanol/water solution

Abstract: Based on experimental NMR data, a model was generated for the conformation of the disulfide-bond-closed cyclic peptide corresponding to the whole V3 loop of the consensus HIV-1 strain in a 20% trifluoroethanol/water solution. The obtained family of structures shows a prominent and well-defined amphipathic alpha helix at the C-terminal end of the peptide from Thr23 to Gln32. A series of turns characterizes the central Gly15-Tyr21 region, while the N-terminal region is poorly defined. Independent experimental da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 63 publications
0
27
0
1
Order By: Relevance
“…Following the beta strand, a short 3 10 G helical turn (Ile P326 , Arg P327 ,and Gln P328 )-the bend of the fishhook-extends toward the light-chain side of the pedestal. Interestingly, it was previously predicted by sequence analysis that the C-terminal region of V3 has a tendency to form a short alpha helix (52), and it was reported that the V3 C-terminal strand could form a helical conformation in an NMR study of a cyclic V3 peptide (53). However, this region of the full-length V3 structures in the context of the gp120 core does not contain any helical conformation (18,54).…”
Section: Resultsmentioning
confidence: 98%
“…Following the beta strand, a short 3 10 G helical turn (Ile P326 , Arg P327 ,and Gln P328 )-the bend of the fishhook-extends toward the light-chain side of the pedestal. Interestingly, it was previously predicted by sequence analysis that the C-terminal region of V3 has a tendency to form a short alpha helix (52), and it was reported that the V3 C-terminal strand could form a helical conformation in an NMR study of a cyclic V3 peptide (53). However, this region of the full-length V3 structures in the context of the gp120 core does not contain any helical conformation (18,54).…”
Section: Resultsmentioning
confidence: 98%
“…NMR studies of isolated V3 peptides show no stable structure in solution, but transient turns exist around GPGR (7-9, 17, 18, 19, 25, 33, 36, 37, 52, 64, 77, 79, 80, 84). NMR studies of peptides modified by cyclization (4,9,33,38,74,(76)(77)(78), by replacement of Ala P316 with the conformationally restricted residue ␣-aminoisobutyric acid (4,25), by glycosylation (36,37,52), through attachment to resin beads (40), through attachment to a bacteriophage viral coat protein (39), and through attachment to carrier proteins, such as bovine pancreatic trypsin inhibitor (81) and MUC1 (22), all show an increased ␤-turn propensity around GP GRAF, while V3 peptides attached to filamentous bacteriophage fd viral coat protein pVIII (39) adopt a double-turn structure similar to that observed in the Fab 59.1-peptide crystal structure (25,26).…”
mentioning
confidence: 99%
“…The population of V3-loop structures and prior distribution: NMR data for V3-loop structure (PDB code 1CE4) (Vranken et al 2001) resulted in 20 models, representing the structural diversity of the loop when viewed at moderate resolution ( Figure 1a). Furthermore, the five existing crown structures (PDB codes 1CE4, 1NJ0, 1B03, 1ACY, and 1K5M) (Ghiara et al 1994;Balbach et al 2000;Vranken et al 2001;Ding et al 2002;Sharon et al 2003; Figure 1b) have provided additional information on the diversity of the crown structure.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the five existing crown structures (PDB codes 1CE4, 1NJ0, 1B03, 1ACY, and 1K5M) (Ghiara et al 1994;Balbach et al 2000;Vranken et al 2001;Ding et al 2002;Sharon et al 2003; Figure 1b) have provided additional information on the diversity of the crown structure. These two sources of structural data can be regarded as samples from the population of the structures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation